Detection of carbapenemase-producing Enterobacterales and the BD Phoenix CPO Detect panel. (3rd August 2019) - Simon, Michaela; Koestler, Josef; Reischl, Udo; Gessner, André; Jantsch, Jonathan
ABSTRACT: Introduction : Treatment options for infections with carbapenem-resistant Enterobacterales are strongly limited. New antimicrobials are not effective against all types of carbapenemases. Therefore, rapid and reliable antimicrobial susceptibility testing and identification of the resistance mechanism are important. Areas covered : We assess several methods to determine carbapenemase production of Enterobacterales in culture and discuss the value of the novel automated BD Phoenix CPO Detect (BDPCPO) panel for the detection and classification of carbapenemases. Expert opinion : The meropenem minimum inhibitory concentration (MIC) range used in the BDPCPO panel includes the EUCAST screening breakpoint for the detection of carbapenemase producers. The phenotypic, inhibitor-based assay for detection of carbapenemase activity in the BDPCPO panel displays high sensitivity for carbapenemase detection while its specificity is modest. Therefore, confirmation testing of positive results is warranted. Nevertheless, implementing the BDPCPO panel has the potential to reduce time-to-result for detection and classification of carbapenemase producers.